Pengaruh Variasi Metode Ekstraksi Jahe dan Serai terhadap Aktivitas Antiinflamasi pada Penghambatan Denaturasi Protein - Faradiba, Faradiba; Syarif, Rezki Amriati Amriati; Khaira, A Tenri Mifta; Alyanti, Tifani Kursya (Faculty of Pharmacy, Universitas Muslim Indonesia, 2024)
The content of secondary metabolites or chemical content in medicinal plants affects pharmacological activity. The level of chemical content is affected by the extraction method. Previous research has been conducted on the extraction of ginger and lemongrass using two methods, which include maceration and ultrasonic. The results obtained are differences in chemical content that have the potential to have anti-inflammatory activity. Ginger (Zingiber officinale) contains chemical compounds, including gingerol, shogaol, and zingeron. linalool, alpha-pinene, and sineol. Lemongrass (Cymbopogon citratus) contains citronellal, citronellol, geraniol, flavonoids, and tannins. The aim of this study was to compare the invitro anti-inflammatory activity of ginger and lemongrass extracts using two extraction methods: maceration and ultrasonic. The research method consists of two stages, i.e. extraction of samples using maceration and ultrasonic methods. The second stage is testing the anti-inflammatory activity against BSA (Bovine Serum Albumin) denaturation of extracts from maceration and ultrasonic methods with the parameter of percentage value to be more than 20%. The results obtained from ginger and lemongrass extracts showed the percentage value of inhibition at concentrations of 10 µg/mL, 12.5 µg/mL, 17.5 µg/mL, and 20 µg/mL are all more than 20%. The ultrasonic extraction of ginger showed a more linear inhibition percentage than the results of maceration. Macerated lemongrass extract showed a more linear percentage inhibition than ultrasonic results.